2022
DOI: 10.3390/app12041850
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing RNA-Seq Gene Expression Data Using Deep Learning Approaches for Cancer Classification

Abstract: Ribonucleic acid Sequencing (RNA-Seq) analysis is particularly useful for obtaining insights into differentially expressed genes. However, it is challenging because of its high-dimensional data. Such analysis is a tool with which to find underlying patterns in data, e.g., for cancer specific biomarkers. In the past, analyses were performed on RNA-Seq data pertaining to the same cancer class as positive and negative samples, i.e., without samples of other cancer types. To perform multiple cancer type classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…Disease sub-type prediction aims at identifying sub-types of patients so that it permits a more accurate assessment of prognosis (Saria and Goldenberg, 2015). Predicting disease sub-types with gene expression data is of great significance in molecular biology (Rukhsar et al, 2022). Accurate classification allows a more efficient and targeted succeeding therapy (Sohn et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Disease sub-type prediction aims at identifying sub-types of patients so that it permits a more accurate assessment of prognosis (Saria and Goldenberg, 2015). Predicting disease sub-types with gene expression data is of great significance in molecular biology (Rukhsar et al, 2022). Accurate classification allows a more efficient and targeted succeeding therapy (Sohn et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Many advanced statistical studies have proposed novel and robust methods for adaptive designs that have shown significant advantages over conventional dose-finding methods. Artificial intelligence and deep learning methods are also promising for clinical trials, but their applications for phase I trials have not been explored yet [2][3][4][5]. Nevertheless, due to these advanced statistical methods, the number of patients requiring highly toxic or non-efficacious doses has decreased significantly, while statistical efficiency has substantially improved.…”
Section: Introductionmentioning
confidence: 99%
“…There are several computational approaches utilized in the bioinformatics field in the last few decades, for example, data mining and pattern recognition, to deal with higher-dimensional problems but still unsuccessful [ 6 ]. Thus, recently, machine learning (ML), a branch of artificial intelligence, has received considerable attention from researchers in gene expression and genomics [ 7 ]. Also, ML is a branch of data science; the main goal is to allow a model for training and learning to make decisions by itself in the future.…”
Section: Introductionmentioning
confidence: 99%